A Review of Economic Instruments Employed for Biodiversity Conservation - Ekpe, Edem Kodzo (Consilience, 2013)
Globally, the use of economic instruments for biodiversity conservation has gained a lot of support. This is because of the concern for the economic well being of people living in and near biodiversity-rich areas. Also, economic drivers are the main threats to biodiversity. This policy of using economic instruments is being used on a case-by-case basis worldwide. A review of their use from a global perspective is important to facilitate learning from issues resulting from their implementation. This article documents and reviews the specific economic instruments being used in different parts of the world for biodiversity conservation. An analysis of the economic instruments using a demand or supply classification suggests that more instruments are targeted at increasing supply of biological resources for human use. A review of literature and field documents was also employed to determine trends in the use of economic instruments for conservation. A major trend observed is the relatively low investments in economic instruments used for biodiversity conservation in developing countries, even though such countries tend to be rich in biodiversity.